Finding the speed of light : the 1676 discovery that dazzled the world - Weston, Mark, 1953- (Tilbury House Publishers, 2019)
Provides a picture book biography of seventeenth-century Danish astronomer Ole Romer who, using only a crude telescope and mechanical timepiece, accidentally managed to measure the speed of light with great accuracy while studying Jupiter's moon. Includes an afterword, a note on Romer's later years, and a timeline.